Acute ischaemic colitis due to hypotension and amoxicillin allergy. Issue 943 (11th May 2004) - Pérez-Carral, C; Carreira, J; Vidal, C
Abstract : A case of acute ischaemic colitis, confirmed by colonoscopy and colon biopsy, caused by IgE mediated allergy to amoxicillin is presented. The damage to the gut seemed to occur as a result of the hypotension suffered during the anaphylactic episode.